Rural Socio-Economic Development through Tourism in Bangladesh: Ways and Means - Saha, Gopal Chandra (American Economic & Social Review, 2020)
This study endeavors to test the effect of promoting of rural tourism in Bangladesh. Rural tourism can offer assistance in forming our society. It can have both positive and negative impacts on rural as well as urban communities. There's a scope of rural tourism in Bangladesh. The government ought to empower private enterprises to advance tourism in rural areas. For creating the rural tourism we ought to get it the rural environment, demography, socio-culture, financial and political foundation of that put. How we will include the country individuals to improve their socio-economic condition. To create a key promoting arranges for rural tourism we ought to get it the target customer, their needs and how to coordinate it with our rural framework. Rural tourism can create a win-win circumstance for both the rural and urban communities.